Heteroborospherene clusters Nin ∈ B40 (n = 1–4) and heteroborophene monolayers Ni2 ∈ B14 with planar heptacoordinate transition-metal centers in η7-B7 heptagons - Hai-Ru Li (Nature Portfolio, 2017)
Abstract With inspirations from recent discoveries of the cage-like borospherene B40 and perfectly planar Co ∈ B18 − and based on extensive global minimum searches and first-principles theory calculations, we present herein the possibility of the novel planar Ni ∈ B18 (1), cage-like heteroborospherenes Nin ∈ B40 (n = 1–4) (2–5), and planar heteroborophenes Ni2 ∈ B14 (6, 7) which all contain planar or quasi-planar heptacoordinate transition-metal (phTM) centers in η7-B7 heptagons. The nearly degenerate Ni2 ∈ B14 (6) and Ni2 ∈ B14 (7) monolayers are predicted to be metallic in nature, with Ni2 ∈ B14 (6) composed of interwoven boron double chains with two phNi centers per unit cell being the precursor of cage-like Nin ∈ B40 (n = 1–4) (2–5). Detailed bonding analyses indicate that Nin ∈ B40 (n = 1–4) (2–5) and Ni2 ∈ B14 (6, 7) possess the universal bonding pattern of σ + π double delocalization on the boron frameworks, with each phNi forming three lone pairs in radial direction (3dz2 2, 3dzx 2, and 3dyz 2) and two effective nearly in-plane 8c-2e σ-coordination bonds between the remaining tangential Ni 3d orbitals (3dx2−y2 and 3dxy) and the η7-B7 heptagon around it. The IR, Raman, and UV-vis absorption spectra of 1–5 are computationally simulated to facilitate their experimental characterizations.